Airway Management and Perioperative Concerns in Acromegaly Patients Undergoing Endoscopic Transsphenoidal Surgery for Pituitary Tumors. Issue 6 (3rd October 2013) - Friedel, Mark E.; Johnston, Doug R.; Singhal, Saurabh; Khalili, Kenan Al; Farrell, Christopher J.; Evans, James J.; Nyquist, Gurston G.; Rosen, Marc R.
Abstract : Objectives: Patients with acromegaly present unique challenges to cranial base surgery and anesthesia teams in the perioperative period, especially with regard to airway management. Abnormal airway anatomy may result from soft tissue hypertrophy and bony alterations. Additional perioperative challenges relate to the management of medical comorbidities. We aim to review perioperative airway concerns in acromegalic patients for the skull base surgeon in order to reduce preventable perioperative complications. Study Design: Case series with chart review. Setting: Tertiary care academic institution. Subjects: Thirty‐two acromegaly patients undergoing endoscopic transsphenoidal pituitary surgery. Results: Videoscopic direct laryngoscopy intubation was required in 7 of 32 patients (21.9%) and fiberoptic intubation in 4 of 32 patients (12.5%). Overall failure rate for first intubation technique used was 12.5% (4/32). Cardiovascular comorbidities (hypertension and conduction abnormalities predominated) were present in 16 of 32 patients (50%), and obstructive sleep apnea, or other respiratory conditions, existed in 12 of 32 patients (37.5%). Conclusions: Acromegaly patients present a particular challenge to the endoscopic skull base surgeon. Despite preoperative anesthesia and otolaryngology evaluation, many of these patients will experience an unanticipated airway challenge during intubation. Preoperative preparation and perioperative awareness of anatomic and physiologic abnormalities of acromegalic patients is essential for successful endoscopic surgery in this unique population.